Testing economic literacy: an overview of measurement instruments of the past 30 years - Welsandt, Nina Charlotte Johanna; Abs, Hermann Josef (JSSE - Journal of Social Science Education, 2023)
Keywords: Systematic review, economic literacy, measurement instruments Measurement instruments often represent only one domain at a time. The focus of test instruments is on querying declarative knowledge. Authentic assessments are rarely being used. Purpose: This paper analyses and classifies currently available English- and German-language measurement instruments for assessing economic literacy. It shows the content-related focuses and gaps of the extracted test instruments, the cognitive level of demand that characterises the instruments, the technical forms of implementation, and the extent to which the lifeworld contexts of test participants were considered. Method: The PSYNDEX, ERIC, German Education Index, and GESIS databases were systematically reviewed, and measurement instruments were examined based on four perspectives of analysis: economic subject dimension, learning psychology, assessment formats and technical design, and authenticity. Findings: Knowledge tests differ substantially from each other. Rather than representing all domains of the subject of economics equally, test instruments usually measure only one domain at a time. The focus of test instruments is on the retrieval of declarative knowledge. Measurement instruments were developed for adults and young people in equal parts. While some test instruments are related to the real world, authentic assessments are an exception.